تقييم جودة البرامج الأكاديمية من وجهة نظر طلبة الدراسات العليا (دراسة ميدانية في كلية الاقتصاد بجامعة تشرين ) - زاهر, بسام; جنبلاط, مادلين (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The study aimed to clarify the reality of academic programs for postgraduate students at the Faculty of Economics at Tishreen University. Quality Assessment of Academic Programs in Tishreen University. To reveal the difficulties and obstacles facing the development of academic programs at Tishreen University. The study population is a graduate student at the Faculty of Economics at Tishreen University. The researcher used the descriptive analytical method to measure and evaluate the quality of the academic programs offered by the Faculty of Economics at Tishreen University. Data analysis was also studied and analyzed using the spss program. After analyzing the data, the study reached a set of results, Dissatisfaction of graduate students with the reality of the quality of the academic programs presented at the Faculty of Economics, dissatisfaction with the reality of curricula and the study plans presented, dissatisfaction with academic support services. هدفت الدراسة إلى بيان واقع البرامج الأكاديمية لطلبة الدراسات العليا في كلية الاقتصاد بجامعة تشرين. بالإضافة إلى بيان درجة تقييم جودة البرامج الأكاديمية في كلية الاقتصاد بجامعة تشرين. والكشف عن الصعوبات والمعوقات التي تواجه تطوير البرامج الأكاديمية في جامعة تشرين. تكون مجتمع الدراسة من طلبة الدراسات العليا في كلية الاقتصاد في جامعة تشرين. استخدمت الباحثة المنهج الوصفي التحليلي لقياس وتقييم جودة البرامج الاكاديمية المقدمة في كلية الاقتصاد في جامعة تشرين، كما تم دراسة وتحليل البيانات باستخدام برنامج spss ، وبعد تحليل البيانات توصلت الدراسة إلى مجموعة من النتائج من أهمها الآتي: عدم رضا طلبة الدراسات العليا عن واقع جودة البرامج الأكاديمية المقدمة في كلية الاقتصاد، عدم الرضا عن واقع المناهج والخطط الدراسية المقدمة، عدم الرضا عن الخدمات الاكاديمية المساندة.